Rancang Bangun Aplikasi Keuangan pada PT. Gunung Putih Putra - Kartina, Riza; Hermizahadiwidastra, Hermizahadiwidastra; Wijaya, Khana (Jurnal Nasional Ilmu Komputer, 2024)
In the increasingly advanced development of the business world, competition between one company and another is getting tighter. The company's financial condition can influence the business's ups and downs. Because, in principle, a company is founded to make a profit. One of the problems that can be solved by implementing an information system in a company is the recording of company financial data. Apart from that, the role of finance in a company is vital and is needed in both large and small companies. The media used to assess a company's financial condition is seen from financial reports. Financial reports result from collecting and processing financial data presented in report form so that users can use it to assess company performance and make the right decisions. The profits earned by the company each year have a direct effect on the company's financial condition. PT. Gunung Putih Putra still uses Microsoft Excel to process financial data. However, the limitations of Microsoft Excel, such as data not being updated and inaccurate, and its lack of user-friendliness, are posing significant challenges. These challenges need to be addressed urgently. The company will be introduced to an application that uses the Object Oriented Programming Language, namely Microsoft Visual Basic 2013.